MPAS-Dev/MPAS-Analysis: v1.2.6 - Asay-Davis, Xylar; Veneziani, Milena; Wolfram, Phillip J.; Roekel, Luke Van; Comeau, Darin; Brady, Riley; Kennedy, Joseph H; Gstreletz; Stephenprice; Turner, Adrian K.; , Kevin; Petersen, Mark; et al. (Zenodo, 2019)
Minor release. Note: Support for python 2.7 has been dropped as of this release Minor Enhancements Turn on Antarctic WOA18 maps by default #632 Add config options to control xarray/dask climatology subtasks #631 Separate shallow and deep color maps for some analysis tasks #643 Add a cryosphere default config file #640 Clean-up Remove support for python 2.7 #630 Address depricated and future warnings from xarray and numpy #629 Move remapping functionality to pyremap package #633 Clarify error message when files are missing #638 Shorten image gallery text for config file name #641 Bug fixes Fix typo in download_natural_earth_110m entry point #626 Fix list of plot fields for main vs. ctrl T-S diagrams #627 Give ann and mon WOA18 output unique file names #635 Fix config copy to HTML #637 Fix compute/plot of regional time series of 2D ocean vars. #639 Contributors @xylar @milenaveneziani